Training Pathology Residents to Practice 21st Century Medicine - W. Stephen Black-Schaffer MA, MD; Jon S. Morrow MD, PhD; Michael B. Prystowsky MD, PhD; Jacob J. Steinberg MD (Elsevier, 2016)
Scientific advances, open information access, and evolving health-care economics are disrupting extant models of health-care delivery. Physicians increasingly practice as team members, accountable to payers and patients, with improved efficiency, value, and quality. This change along with a greater focus on population health affects how systems of care are structured and delivered. Pathologists are not immune to these disruptors and, in fact, may be one of the most affected medical specialties. In the coming decades, it is likely that the number of practicing pathologists will decline, requiring each pathologist to serve more and often sicker patients. The demand for increasingly sophisticated yet broader diagnostic skills will continue to grow. This will require pathologists to acquire appropriate professional training and interpersonal skills. Today's pathology training programs are ill designed to prepare such practitioners. The time to practice for most pathology trainees is typically 5 to 6 years. Yet, trainees often lack sufficient experience to practice independently and effectively. Many studies have recognized these challenges suggesting that more effective training for this new century can be implemented. Building on the strengths of existing programs, we propose a redesign of pathology residency training that will meet (and encourage) a continuing evolution of American Board of Pathology and Accreditation Council for Graduate Medical Education requirements, reduce the time to readiness for practice, and produce more effective, interactive, and adaptable pathologists. The essence of this new model is clear definition and acquisition of core knowledge and practice skills that span the anatomic and clinical pathology continuum during the first 2 years, assessed by competency-based metrics with emphasis on critical thinking and skill acquisition, followed by individualized modular training with intensively progressive responsibility during the final years of training. We anticipate that implementing some or all aspects of this model will enable residents to attain a higher level of competency within the current time-based constraints of residency training.